Clinical features and specific lgE in babies and children with cow's milk allergy - Syawitri P. Siregar; Ida Mardiati; Arwin P. Akib (Indonesian Pediatric Society, 1999)
A discriptive prospective study was done on babies & children not olderthan 3 years of age who came to Pediatric Allergy & Immunology Clinic, Medical School, University of Indonesia - Cipto Mangunkusumo Hospital, Jakarta, during the period of April I 996-March I 997. Screening test included interview, physical examination elimination and open provocation. The aim of the study was to determine clinical features and specific lgE of babies and children with cow's milk allergy (CMA). Among 541 patients, 18 were diagnosed as CMA. The most common clinical symptoms was cronic and recurrent cough (CFC), while only 5 patients were suffering from diarrhea. Specific IgE examination gave positive results on 7 patients, skin tests were positive in 11 patients, and increased total lgE count were found in 13 patients. All CMA patients had family history of atopies.